TAFSSA District Agrifood Systems Assessment in India 2023: Retail Survey - International Rice Research Institute; International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at advancing equitable access to sustainable healthy diets, enhancing farmers' livelihoods and resilience, and conserving natural resources such as land, air, and water across South Asia. The TAFSSA district agrifood systems assessment seeks to establish a robust, accessible, and integrated evidence base that connects farm production, market access, dietary patterns, climate risk responses, and natural resource management, with gender considerations integrated throughout. The assessment focuses on rural areas in Bangladesh, India, and Nepal, utilizing a district-level, multi-year approach. Data was collected between February and June 2023 in the Nalanda district of India. The survey encompassed 50 villages in the district, focusing on formal and informal retail shops operating within the sampled villages. The types of retail shops included local grocery stores and specialized shops selling meat, fish, eggs, or dairy products. The survey utilized pretested, structured questionnaires divided into three distinct modules: 1. Interview-Based Module: Captured vendor information, assortments of essential goods, availability, resilience, food sourcing, food wastage, and dimensions of access and protection. 2. Observation + Photo Module: Documented market information, infrastructure, and aspects related to food quality, safety, and hygiene. 3. Food List Module: Recorded the availability and prices of a comprehensive list of food items found in the area